2006
DOI: 10.1002/pmic.200600076
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone radiation causes changes in gene and protein expression in human endothelial cell lines and the response seems to be genome‐ and proteome‐dependent

Abstract: We have examined in vitro cell response to mobile phone radiation (900 MHz GSM signal) using two variants of human endothelial cell line: EA.hy926 and EA.hy926v1. Gene expression changes were examined in three experiments using cDNA Expression Arrays and protein expression changes were examined in ten experiments using 2-DE and PDQuest software. Obtained results show that gene and protein expression were altered, in both examined cell lines, in response to one hour mobile phone radiation exposure at an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 20 publications
2
67
2
1
Order By: Relevance
“…We have previously determined that the 900 MHz GSM mobile phone radiation signal alters expression of several tens of proteins in the human endothelial cell line EA.hy926 (Leszczynski, et al, 2002;Nylund and Leszczynski, 2004;Nylund and Leszczynski, 2006). In the present study we have examined whether the 1800 MHz GSM mobile phone radiation signal exposure will also affect protein expression in EA.hy926 cells.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously determined that the 900 MHz GSM mobile phone radiation signal alters expression of several tens of proteins in the human endothelial cell line EA.hy926 (Leszczynski, et al, 2002;Nylund and Leszczynski, 2004;Nylund and Leszczynski, 2006). In the present study we have examined whether the 1800 MHz GSM mobile phone radiation signal exposure will also affect protein expression in EA.hy926 cells.…”
Section: Introductionmentioning
confidence: 92%
“…Experimental data obtained from our study indicated that 1800 MHz of EMR exposure for 6 weeks (2 hrs. /day) resulted in mutation in BRCA1 and TP53 genes [ [31] found that EMR caused different effects on c-Fos gene expression in the rat brain, Nylund & Leszezynski [32] showed that gene and protein expression were altered, in two variants of human endothelial cell line, in response to one hour mobile phone radiation exposure. Karien, et al [33] showed that the EMR alters protein expression in human endothelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al (2005) used the serial analysis of gene expression (SAGE) technique and found that 2.45 GHz RF radiation at a 10-W/kg SAR for 2∼6 h affected the expression of 221 genes, including apoptosis-related genes and cell cycle genes, in human HL-60 cells without a significant increase of HSP expression. Nylund et al (2006) reported that two variants of a human endothelial cell line responded differently to 900 MHz GSM signal mobile phone radiation (Nylund et al, 2006). With regard to the effect of RF exposure to rat brain, Belyaev et al (2006) reported that GSM at 915 MHz induced no detectable DNA double-stranded breaks or changes in chromatin conformation but affected the expression of genes related to neurotransmitter regulation, blood brain barrier, and melatonin production in rat brain cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies on the biological effects of RF exposure could not detect any molecular changes, some reports demonstrated RF-specific gene expression (Belyaev et al, 2006;Lee et al, 2005;Nylund et al, 2006). For example, Lee et al (2005) used the serial analysis of gene expression (SAGE) technique and found that 2.45 GHz RF radiation at a 10-W/kg SAR for 2∼6 h affected the expression of 221 genes, including apoptosis-related genes and cell cycle genes, in human HL-60 cells without a significant increase of HSP expression.…”
Section: Introductionmentioning
confidence: 99%